Policies to keep and expand the option of concentrating solar power for dispatchable renewable electricity - Lilliestam, Johan; Barradi, Touria; Caldés, Natalia; Gomez, Marta; Hanger, Susanne; Kern, Jürgen; Komendantova, Nadejda; Mehos, Mark; Hong, Wai Mun; Wang, Zhifeng; Patt, Anthony (Energy Policy, 2018)
Concentrating solar power (CSP) is one of the few renewable electricity technologies that can offer dispatchable electricity at large scale. Thus, it may play an important role in the future, especially to balance fluctuating sources in increasingly renewables-based power systems. Today, its costs are higher than those of PV and wind power and, as most countries do not support CSP, deployment is slow. Unless the expansion gains pace and costs decrease, the industry may stagnate or collapse, and an important technology for climate change mitigation has been lost. Keeping CSP as a maturing technology for dispatchable renewable power thus requires measures to improve its short-term economic attractiveness and to continue reducing costs in the longer term. We suggest a set of three policy instruments – feed-in tariffs or auctions reflecting the value of dispatchable CSP, and not merely its cost; risk coverage support for innovative designs; and demonstration projects – to be deployed, in regions where CSP has a potentially large role to play. This could provide the CSP industry with a balance of attractive profits and competitive pressure, the incentive to expand CSP while also reducing its costs, making it ready for broad-scale deployment when it is needed.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Concentrating solar power; Innovation; Policy design; Policy support; Solar thermal power